(untitled) - Ashmore, Wendy (Boston, MA., 2006)
The book introduces the techniques, methods, and theoretical frameworks of contemporary archaeology. There are a lot of illustrative examples and case studies that present a temporal and geographic balance of both Old and New World sites. Abundant student aids include maps of archaeological areas, extensive illustrations, chapter introductions and summaries, a guide to further reading at the end of each chapter, a glossary, a bibliography, and an index.
Keywords: Archaeology